Barriers to wildlife movement in straits: Problematizing habitat connectivity across marine ecosystems. (July 2022) - Lott, Alexander
Abstract: The innovative development of the legal regime of straits has prevented the erection of 'sovereignty-barriers' to the movement of humans in and above straits. However, it overlooks to a great extent the significance of straits for marine organisms and birds. This article examines if it is necessary to supplement the legal regime of straits with rules that would allow circumnavigating 'sovereignty-barriers' also for wildlife movement considering the obligation to protect and preserve the marine environment. The main users of straits are not humans, but rather marine species. They rely on straits for moving from one ecosystem to another. That perspective to straits shifts the emphasis away from anthropocentric connectivity. It raises a question about the need to update the current navigation-oriented legal regime of straits with new wildlife-centric rules. This implies an additional scrutiny on human activities that have a significant negative effect on marine organisms and the fragile marine environment of straits. A wildlife-centred approach enables to reconsider the appropriateness of some human uses of the seas that are environmentally hazardous, but still relatively commonplace in straits. It is possible to facilitate the unimpeded movement of marine species through straits by the prohibition of some detrimental maritime practices that have a reasonable alternative. Such practices include, e.g., the detonation of naval mines in clearance operations, the construction of such causeways that are impassable for marine species, and the use of overhead power lines in straits. In addition, limits could be set to the use of sonars and to the speed of ships in straits. Highlights: Straits connect large marine ecosystems with one another. Law does not guarantee safe passage through straits for marine species or birds. Physical, acoustic, and chemical barriers obstruct wildlife movement in straits. Often, this is due to the lack of awareness and ignorance of alternatives. There is a need for a global ban on man-made barriers that make straits impassable.